Characterising DSCATT: A case series of Australian patients with debilitating symptom complexes attributed to ticks. (August 2022) - Schnall, Jesse; Oliver, Georgina; Braat, Sabine; Macdonell, Richard; Gibney, Katherine B; Kanaan, Richard A
Objectives(s): To characterise the clinical profile, aetiology and treatment responsiveness of 'Australian Lyme', or Debilitating Symptom Complexes Attributed to Ticks. Methods: Single-centre retrospective case analysis of patients referred to the Infectious Diseases Unit at Austin Health – a tertiary health service in Heidelberg, Australia – between 2014 and 2020 for investigation and treatment of suspected Debilitating Symptom Complexes Attributed to Ticks. Patients were included if they had debilitating symptoms suggested by either themselves or the referring clinician as being attributed to ticks. Results: Twenty-nine Debilitating Symptom Complexes Attributed to Ticks cases were included in the analysis. Other than Lyme disease (83%), the most common prior medical diagnoses were Epstein–Barr virus (38%), chronic fatigue syndrome (28%) and fibromyalgia (24%). Prior histories of anxiety (48%) and depression (41%) were common. The most frequently reported symptoms included fatigue (83%), headache (72%) and arthralgia (69%). National Association of Testing Authorities/Royal College of Pathologists of Australasia–accredited serology was not diagnostic of acute infective causes, including Lyme disease, in any patient. Of 25 cases with available data, 23 (92%) had previously been prescribed antimicrobials, with 53% reporting benefit from them. The most common diagnoses made by our hospital were chronic fatigue syndrome (31%), migraines (28%) and fibromyalgia (21%). Only one patient's symptoms were not accounted for by other diagnoses. Conclusion: This is the first case series of patients with Debilitating Symptom Complexes Attributed to Ticks. They had high rates of other medically unexplained syndromes, and no evidence of acute Lyme disease, or any common organic disease process. Debilitating Symptom Complexes Attributed to Ticks remains medically unexplained, and may therefore be due to an as yet unidentified cause, or may be considered a medically unexplained syndrome similar to conditions such as chronic fatigue syndrome.